Application of Media Relations in Maintaining the Image in Diskominfo DIY - Pelawi, Mei Syella Br; Lestari, Rani Dwi; Yusfiarista, Erlika (Formosa Journal of Applied Sciences, 2025)
The role of media relations and public relations at Diskominfo DIY is quite important, where the role is to publish information quickly, either directly or through websites and other social media. This research uses several indicators in maintaining the image at Diskominfo DIY from Frank Jefkins' theory of serving the media, services provided by public relations by providing press releases, researchers have made observations, where public relations provides services to the media in the form of press releases which are useful for answering and also responding to planned or unplanned events, this proves that Diskominfo DIY public relations practitioners apply by serving the media, where the services provided by public relations to the media are in accordance with what is needed by the media in any situation.